Glycosaminoglycan analogs as a novel anti-inflammatory strategy - Proudfoot, Amanda E. (Frontiers in Immunology, 2012)
Heparin, a glycosaminoglycan (GAG), has both anti-inflammatory and anti-coagulant properties. The clinical use of heparin against inflammation, however, has been limited by concerns about increased bleeding. While the anticoagulant activity of heparin is well understood, its anti-inflammatory properties are less so. Heparin is known to bind to certain cytokines, including chemokines, small proteins which mediate inflammation through their control of leukocyte migration and activation. Molecules which can interrupt the chemokine-GAG interaction without inhibiting coagulation could therefore represent a new class of anti-inflammatory agents. In the present study, two approaches were undertaken, both focusing on the heparin-chemokine relationship. In the first, a structure based strategy was used: after an initial screening of potential small molecule binders using protein NMR on a target chemokine, binding molecules were optimized through structure-based design. In the second approach, commercially available short oligosaccharides were polysulfated. In vitro, these molecules prevented chemokine-GAG binding and chemokine receptor activation without disrupting coagulation. However, in vivo, these compounds caused variable results in a murine peritoneal recruitment assay, with a general increase of cell recruitment. In more disease specific models, such as antigen-induced arthritis and delayed-type hypersensitivity, an overall decrease in inflammation was noted, suggesting that the primary anti-inflammatory effect may also involve factors beyond the chemokine system.